Antibacterial Activity of Glycine max L. Seeds Using Different Extracts - Firas Abbas Al-Bayati (College of Education for Pure Sciences, 2007)
Abstract In the present study, antibacterial properties of three different extracts from Glycine max L. seeds were screened against four types of Gram-positive and negative bacteria Staphylococcus aureus, Bacillus cereus, Klebsiella pneumoniae and Pseudomonas aeruginosa using agar-well diffusion method and comparing with standard antibiotics Chloramphenicol, Cephalexin, Tetracycline and Gentamycin. The ethanol extract demonstrated good inhibitory effects against most tested bacteria using the extract concentration 200mg/cm3 compared with chloroform and petroleum ether extracts which gave clear inhibitory effect against Ps. aeruginosa using the same extract concentration the study also revealed the complete resistance of B. cereus towards chloroform and petroleum ether extracts but was inhibited using all ethanol extract concentrations and the proportion between inhibitory effect and extract concentration was direct.